2018
DOI: 10.1016/j.jenvrad.2018.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and fate of 129I in the seabed sediment off Fukushima

Abstract: Highlights  Concentration of 129 I in seabed sediment off Fukushima is reported for the first time  Deposition of the FDNPP accident-derived 129 I to the seafloor was 0.36 ± 0.13 GBq  Until October 2013, 129 I activity in sediment increased in the shelf-edge region  Remobilization of 129 I near the seafloor likely affected the sequential accumulation  The accident-derived 129 I is considered to negligibly affect the benthic ecosystem

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…42,43 The ratio of 129 I/ 137 Cs in suspended particles of rivers is lower than that of marine sediments and should be considered as another process for selectively supplying 137 Cs to coastal seawater. 32 Although there exist samples that show elevated 90 Sr values during events of high wind or precipitation, there is not a significant relationship between high wind or precipitation with elevated 90 Sr concentrations (Figure 5). Perhaps this is not surprising, as the amount of 90 Sr deposited to land is small compared to 137 Cs.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…42,43 The ratio of 129 I/ 137 Cs in suspended particles of rivers is lower than that of marine sediments and should be considered as another process for selectively supplying 137 Cs to coastal seawater. 32 Although there exist samples that show elevated 90 Sr values during events of high wind or precipitation, there is not a significant relationship between high wind or precipitation with elevated 90 Sr concentrations (Figure 5). Perhaps this is not surprising, as the amount of 90 Sr deposited to land is small compared to 137 Cs.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, it has been found that coastal sediments near the FDNPPs selectively release 129 I over 137 Cs. 32 The most likely explanation is ongoing variable releases of 129 I while 137 Cs is more effectively being removed via radionuclide decontamination systems at the FDNPPs, thereby leading to an increase in the 129 I/ 137 Cs ratio. The 129 I/ 90 Sr ratios (Figure 3d) were similarly higher in 2016 (36 ± 7 × 10 −5 ) than 2015 (9 ± 1 × 10 −5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 129 I/ 127 I atom ratios of [2.0 ± 1.5] × 10 −10 and [0.49 ± 0.22] × 10 −10 were found in the seawater samples collected during the cutting period and 2009 to 2010, respectively, with statistically significant differences between each other according to the U test (p < 0.01). Although the data after 2010 were available, those were possibly affected by 129 I released from the Fukushima Dai-ichi Nuclear Power Plant accident [5] and were excluded here. In addition, it should be noted that small scale discharge of 129 I (~ 1/10 of the maximum discharge rate during the cutting period) continued during 2009 to 2010 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since 129 I has a long half-life of 1.57 × 10 7 years, the environmental behavior of 129 I should be studied to ensure the safety of the local population around the reprocessing plant and also for public acceptance of such plants. Additionally, 129 I has become an indicator estimating behaviors of other anthropogenic radionuclides, such as 131 I, in coastal areas [3][4][5]. Therefore, it is important to understand the dynamics of 129 I in aquatic environments.…”
Section: Introductionmentioning
confidence: 99%